2015
DOI: 10.1186/s12937-015-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the detection and nutritional management of high-output stomas

Abstract: IntroductionAn issue of recent research interest is excessive stoma output and its relation to electrolyte abnormalities. Some studies have identified this as a precursor of dehydration and renal dysfunction. A prospective study was performed of the complications associated with high-output stomas, to identify their causes, consequences and management.Materials and methodsThis study was carried out by a multidisciplinary team of surgeons, gastroenterologists, nutritionists and hospital pharmacists. High-output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
103
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 24 publications
0
103
0
12
Order By: Relevance
“…EPA counter-regulates leukocyte-mediated tissue injury and proinflammatory gene expression (15). It has been reported that nutritional management is important in HOI treatment (7,8). Recent studies have reported that ProSure™ (Abbot Japan Co., Ltd, Tokyo, Japan), an EPA-containing supplement, affects the nutritional status and quality of life in advanced cancer patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPA counter-regulates leukocyte-mediated tissue injury and proinflammatory gene expression (15). It has been reported that nutritional management is important in HOI treatment (7,8). Recent studies have reported that ProSure™ (Abbot Japan Co., Ltd, Tokyo, Japan), an EPA-containing supplement, affects the nutritional status and quality of life in advanced cancer patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…High-output ileostomy (HOI) is often observed and is accompanied by electrolyte abnormalities and/or stoma complications (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…High output of enteric contents is a common sequela of both double enterostomy (DES) of the small bowel and a subtype of enterocutaneous fistula with an exposed external orifice, termed enteroatmospheric fistula (EAF) . High outputs are known to precede multiple complications including dehydration and renal impairment, electrolyte disturbances, malnutrition, and intestinal failure (IF) . Mortality has been reported to be as high as 30% in high‐output EAFs compared with 6% having low output …”
Section: Introductionmentioning
confidence: 99%
“…1 High outputs are known to precede multiple complications including dehydration and renal impairment, electrolyte disturbances, malnutrition, and intestinal failure (IF). [2][3][4] Mortality has been reported to be as high as 30% in high-output EAFs compared with 6% having low output. [5][6][7] Patients with high-output DES or EAF are commonly managed in the tertiary care setting, often as inpatients in specialist colorectal or IF units.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, this is due to a high‐output ECF or enterostomy. Although different definitions are used in literature, generally an ECF producing over 500 mL/24 h or an enterostomy producing over 1500 mL/24 h is considered as high output. Three types of intestinal failure can be distinguished.…”
Section: Introductionmentioning
confidence: 99%